Antimicrobial Resistance: New Mechanisms, Surveillance Strategies and Novel Approaches (Indian Journal of Public Health Research & Development, 2026)
Antimicrobial resistance (AMR) represents a critical and escalating global public health threat, driven primarilyby the overuse and misuse of antibiotics in human medicine, agriculture, and animal production. The emergenceand dissemination of multidrug-resistant (MDR) organisms are further accelerated by horizontal gene transfer,environmental reservoirs, and inadequate infection prevention and control practices. Recent global estimatesindicate that bacterial AMR was directly responsible for 1.27 million global deaths in 2019 and contributed to 4.95million deaths, with projections suggesting substantial increases in mortality and economic burden if effectiveinterventions are not implemented.This review summarizes the major molecular mechanisms underlying antimicrobial resistance, includingenzymatic drug inactivation, target modification, porin modifications, efflux pump overexpression, andbiofilm formation. Innovative approaches, including phage therapy, CRISPR-based antimicrobials, monoclonalantibodies, nanomaterials, vaccination and artificial intelligence (AI) are highlighted as promising next-generationalternatives.Despite scientific advances, the antibiotic development pipeline remains constrained by economic and regulatorychallenges. Sustained research and development, strengthened antimicrobial stewardship, global surveillance,and collaborative industry-academic partnerships are essential to preserve existing therapies and ensure futuretreatment options against MDR pathogens.
Keywords: Antimicrobial resistance, Antibiotic stewardship, Novel approaches, Phage therapy, Antimicrobial peptides.